EEG activity evoked in preparation for multi-talker listening by adults and children - Holmes, Emma; Kitterick, Pádraig T.; Summerfield, A. Quentin (Elsevier, 2016)
Selective attention is critical for successful speech perception because speech is often encountered in the presence of other sounds, including the voices of competing talkers. Faced with the need to attend selectively, listeners perceive speech more accurately when they know characteristics of upcoming talkers before they begin to speak. However, the neural processes that underlie the preparation of selective attention for voices are not fully understood. The current experiments used electroencephalography (EEG) to investigate the time course of brain activity during preparation for an upcoming talker in young adults aged 18-27 years with normal hearing (Experiments 1 and 2) and in typically-developing children aged 7-13 years (Experiment 3). Participants reported key words spoken by a target talker when an opposite-gender distractor talker spoke simultaneously. The two talkers were presented from different spatial locations (±30° azimuth). Before the talkers began to speak, a visual cue indicated either the location (left/right) or the gender (male/female) of the target talker. Adults evoked preparatory EEG activity that started shortly after (<50 ms) the visual cue was presented and was sustained until the talkers began to speak. The location cue evoked similar preparatory activity in Experiments 1 and 2 with different samples of participants. The gender cue did not evoke preparatory activity when it predicted gender only (Experiment 1) but did evoke preparatory activity when it predicted the identity of a specific talker with greater certainty (Experiment 2). Location cues evoked significant preparatory EEG activity in children but gender cues did not. The results provide converging evidence that listeners evoke consistent preparatory brain activity for selecting a talker by their location (regardless of their gender or identity), but not by their gender alone.